Wasting Away: To Sludge or Not to Sludge? - L Nicolle; M Miller (Canadian Journal of Infectious Diseases)
Following a century of high standards of sanitation, food and water safety in North America are often taken for granted. Recent outbreaks of illness attributed to food and water contamination, however, have challenged this complacency. Now, sludge is added to the list of concerns. Sewage sludge is the muddy substance that remains after the treatment of municipal sewage. This material includes not only human waste, but also household and industrial toxic wastes disposed of in local sewers. Federal and provincial Canadian regulations support the use of this material as fertilizer, within acceptable guidelines, as does the Environmental Protection Agency in the United States. The safety of sludge, however, is questioned by some individuals and groups. Specifically, the risk of infectious agents and toxins to workers or other exposed individuals, and the potential for heavy metals and organic chemicals to be transferred from sludge-treated fields into crops are concerns.